Analisis Dampak Neraca Pembayaran International Di Indonesia Pada Era Digitalisasi - Sri Wahyuni; Liza Afkarin; Ahmad Fuji Sugiyarto; Nurul Erda; Rini Puji Astuti (CV. ITTC INDONESIA, 2024)
Digitalization has changed many sectors of the world economy, including Indonesia's balance of international payments, along with advances in information and communication technology. Faster, safer, and more efficient economic transactions have been facilitated by digitalization, which changes the way countries interact with each other. So that each country will be easier and freer in accessing trade in exports and imports, making it easier to manage financial flows, and facilitate investment. This study aims to determine the impact of the International Balance of Payments in Indonesia on Eradigitalization. This research uses a descriptive qualitative method with a literature review approach through collecting and reviewing academic studies. The results of the study prove that the impact of Indonesia's international balance of payments in Eradigitalization has a positive impact on the Balance of Trade, Financial Flows, and Investment across countries.